KEKUATAN TARIK DAN PEMANJANGAN SAAT PUTUS KOMPOSIT POLI ASAM LAKTAT (PLA) DAN SERAT SELULOSA DENGAN PENAMBAHAN PEMLASTIS - fatruyani, . (Universitas Tanjungpura, 2017)
Biodegradable plastic is a plastic that can be used like conventional plastic, the advantage of plasticis it can be destroyed by the activity of microorganisms become water and carbon diokside. Utilization of Polylactic acid (PLA) as alternative material is conventional plastic is very potential because PLA has decomposble properties in the nature and can be made from renewable sources. Besides the advantage of PLA is easily decomposed and made from renewable sources, PLA also has the weakness such as fragile, therefore adding a plasticizer glycerol is needed. In this researh biodegradableplastic was made by using PLA and glycerol. Glycerol was added of 0, 10, 20 and 30 PHR (Per Hundreet Resin). Testingwas done by using Universal Testing Machine Merk Shimadzu load-cell speed 1 mm/minute and gauge lenght 70 mm based on standard ASTM D-638-02a. Lenght of sample 110 mm, widht 6 mm thick 0,7 mm. This experiment was repitation from three replications. The result of research showed that the highest value of tensile strenght and MOE composit PLA was note in the composite of PLA with out glycerolwith values 44,03 MPa and 3,39 GPa respetivelly.Keyword : Glycerol, Mechanical Properties, Plastic Biodegradable, Polylactic Acid Composite.